Frequency and clinical characteristics of hypophysitis and hypopituitarism in patients undergoing immunotherapy – A systematic review - Jacques, Juliana Prudêncio; Valadares, Luciana Pinto; Moura, Adriana Castelo; Oliveira, Maria Regina Fernandes; Naves, Luciana Ansaneli (Frontiers in Endocrinology, 2023)
Objective: To describe the frequency of hypophysitis and hypopituitarism in cancer patients who are undergoing antineoplastic treatment with immunotherapy, as well as to describe the clinical, epidemiological, and demographic characteristics of these patients. Methods: A systematic search of the literature in PubMed, Embase, Web of Science, ClinicalTrials.gov and Cochrane Controlled Register of Trials took place on May 8 and 9, 2020. Randomized and nonrandomized clinical trials, cohort studies, case-control studies, case series and case reports were included. Results: A total of 239 articles were obtained, in which 963 cases of hypophysitis and 128 cases of hypopituitarism were found in a treated population of 30,014 individuals (3.20% and 0.42% of the evaluated population, respectively). In the cohort studies, the incidence of hypophysitis and hypopituitarism ranged from 0% to 27.59% and from 0% to 17.86%, respectively. In the non-randomized clinical trials, the incidence of hypophysitis and hypopituitarism ranged from 0% to 25% and from 0% to 14.67%, and in randomized clinical trials from 0% to 16.2% and from 0% to 33.33%. The most common hormonal changes were in the corticotrophic, thyrotrophic and gonadotrophic axes. The main magnetic resonance imaging (MRI) findings were enlargement of the pituitary gland and enhanced contrast uptake. The main symptoms presented by patients with hypophysitis were fatigue and headache. Conclusion: The present review reported a frequency of hypophysitis and hypopituitarism of 3.20% and 0.42%, respectively, in the evaluated population. The clinical-epidemiological characteristics of patients affected by hypophysitis were also described.